If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2senx + -3cotx = 0 Reorder the terms: -3cotx + 2ensx = 0 Solving -3cotx + 2ensx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2ensx' to each side of the equation. -3cotx + 2ensx + -2ensx = 0 + -2ensx Combine like terms: 2ensx + -2ensx = 0 -3cotx + 0 = 0 + -2ensx -3cotx = 0 + -2ensx Remove the zero: -3cotx = -2ensx Divide each side by '-3otx'. c = 0.6666666667eno-1st-1 Simplifying c = 0.6666666667eno-1st-1
| 2.5x/12x | | 155=5(-6a-5) | | -2+3y-8y+3x= | | 6-5n=-(n-6) | | 40r-5r+7r= | | (2x+5)=x+3 | | 4x(3x-1)-6(2x+1)= | | 3/10=-8/5-n | | 30/7x=-255/28 | | sec(2x)+tan(x)=1 | | a-(-16)=11 | | 5c^3-15c^2+10c=0 | | 3r+9=-3(8r-3) | | 3r+9=24+9 | | 7+15x+2x^2= | | log(5)(5x+6)=2 | | tanx=cotx | | 0.5r+7=9 | | -4c+4c-2= | | -5(7r+5)=31-7r | | 5x^2-2x-16=2x^2+6x | | 2cos(2x)-cos(x)=0 | | logx+2(0)16=4 | | 7r^2-19r-14=-3r+1 | | 30x^2-20x-28=5x^2+4 | | X/2=62 | | V/2=62 | | 3x(-7x^4y)= | | 25n^2+4n-1=1-5n^2 | | 1.13=ln(x/1) | | -6(8-8p)-7=-15+8p | | 25n^2+4n-1=1-5n |